Understanding Optimum Fluoride Intake from Population-Level Evidence. (March 2018) - Spencer, A.J.; Do, L.G.; Mueller, U.; Baines, J.; Foley, M.; Peres, M.A.
Policy on fluoride intake involves balancing caries against dental fluorosis in populations. The origin of this balance lies with Dean's research on fluoride concentration in water supplies, caries, and fluorosis. Dean identified cut points in the Index of Dental Fluorosis of 0.4 and 0.6 as critical. These equate to 1.3 and 1.6 mg fluoride (F)/L. However, 1.0 mg F/L, initially called a permissible level, was adopted for fluoridation programs. McClure, in 1943, derived an "optimum" fluoride intake based on this permissible concentration. It was not until 1944 that Dean referred to this concentration as the "optimal" concentration. These were critical steps that have informed health authorities through to today. Several countries have derived toxicological estimates of an adequate and an upper level of intake of fluoride as an important nutrient. The US Institute of Medicine (IOM) in 1997 estimated an Adequate Intake (AI) of 0.05 mg F/kg bodyweight (bw)/d and a Tolerable Upper Intake Level (UL) of 0.10 mg F/kg bw/d. These have been widely promulgated. However, a conundrum has existed with estimates of actual fluoride intake that exceed the UL without the expected adverse fluorosis effects being observed. Both the AI and UL need review. Fluoride intake at an individual level should be interpreted to inform more nuanced guidelines for individual behavior. An "optimum" intake should be based on community perceptions of caries and fluorosis, while the ultimate test for fluoride intake is monitoring caries and fluorosis in populations.